Nestor : bibliography of Aegean prehistory and related areas - University of Cincinnati - Department of Classics (2001)
[Dt.:] Bibliographie zur Archäologie der ägäischen Bronzezeit verwandten Themengebieten. Über eine Recherchemaske ist die Bibliographie nach verschiedenen Kriterien durchsuchbar. Linksammlung zu Projekten zur ägäischen Bronzezeit. Newsmeldungen zu Publikationen, Stiftungen und Tagungen. - [Engl.:] This website is the online version of the Nestor, the bibliography of the Aegean Bronze Age and related topics, edited by the Department of Classics of the University of Cincinnati (Ohio). It provides the possibility of a literature search by author, title, year etc. There is also the possibility to conduct a meta-search within all fields. The literary references are dated between 1957 and 2011 and are being updated regularly. The website also informs about scholarships, recent publications and conferences.